Evaluation of Quality, Antioxidant Capacity, and Digestibility of Chickpea (Cicer arietinum L. cv Blanoro) Stored under N2 and CO2 Atmospheres - Liliana Maribel Perez-Perez; José Ángel Huerta-Ocampo; Saúl Ruiz-Cruz; Francisco Javier Cinco-Moroyoqui; Francisco Javier Wong-Corral; Luisa Alondra Rascón-Valenzuela; Miguel Angel Robles-García; Ricardo Iván González-Vega; Ema Carina Rosas-Burgos; María Alba Guadalupe Corella-Madueño; Carmen Lizette Del-Toro-Sánchez (Molecules, 2021)
The aim of this work was to monitor the quality, antioxidant capacity and digestibility of chickpea exposed to different modified atmospheres. Chickpea quality (proximal analysis, color, texture, and water absorption) and the antioxidant capacity of free, conjugated, and bound phenol fractions obtained from raw and cooked chickpea, were determined. Cooked chickpea was exposed to N2 and CO2 atmospheres for 0, 25, and 50 days, and the antioxidant capacity was analyzed by DPPH (2,2′-diphenyl-1-picrylhydrazyl), ABTS (2,2′-azino-bis-[3ethylbenzothiazoline-6-sulfonic acid]), and total phenols. After in vitro digestion, the antioxidant capacity was measured by DPPH, ABTS, FRAP (ferric reducing antioxidant power), and AAPH (2,2′-Azobis [2-methylpropionamidine]). Additionally, quantification of total phenols, and UPLC-MS profile were determined. The results indicated that this grain contain high quality and high protein (18.38%). Bound phenolic compounds showed the highest amount (105.6 mg GAE/100 g) and the highest antioxidant capacity in all techniques. Cooked chickpeas maintained their quality and antioxidant capacity during 50 days of storage at 4 and −20 °C under a nitrogen atmosphere. Free and conjugated phenolic compounds could be hydrolyzed by digestive enzymes, increasing their bioaccessibility and their antioxidant capacity during each step of digestion. The majority compound in all samples was enterodiol, prevailing the flavonoid type in the rest of the identified compounds. Chickpea contains biological interest compounds with antioxidant potential suggesting that this legume can be exploited for various technologies.